The water vapor foreign-continuum in the 1.6 µm window by CRDS at room temperature. (May 2020) - Mondelain, D.; Vasilchenko, S.; Kassi, S.; Campargue, A.
Highlights: First water vapour foreign-continuum measurements at 296 K in the 1.6 µm window. CRDS loss rates were measured during pressure ramps of humidified air. Cross-sections are provided for 15 spectral points between 5700 and 6750 cm −1 . Derived foreign cross-sections are larger than the semi-empirical MT_CKD values. Abstract: Water vapour foreign-continuum absorption cross-sections, CF, are measured for the first time at room temperature in the 1.6 µm transparency window, of importance for atmospheric applications. The measurements are performed by cavity ring down spectroscopy (CRDS) at 15 selected spectral data points. These data, covering the 5700–6640 cm −1 spectral range, are derived from the variation of the absorption signal during pressure ramps of humidified air up to 1 atm with a typical 1% water vapour relative concentration. The foreign-continuum absorption was obtained as the excess of the measured loss rate compared to the sum of the loss rate measured with dry air, the local water monomer contribution and the self-continuum absorption. CF values were derived from the linear dependence of the foreign-continuum absorption with the product of the partial pressures of water vapour and air. The semi-empirical MT_CKD CF values are found significantly underestimated in the centre of the window. Graphical abstract: Image, graphical abstract